Integration of biophysical and biological approaches to validate fragment-like compounds targeting L,D-transpeptidases from Mycobacterium tuberculosis - Andrés Libreros-Zúñiga, Gerardo [UNESP]; Pavão e Pavão, Danilo; de Morais Barroso, Vinicius; Cristina de Moraes Roso Mesquita, Nathalya; Fehelberg Pinto Braga, Saulo; Oliva, Glaucius; Salgado Ferreira, Rafaela; Ishida, Kelly; Vinicius Bertacine Dias, Marcio [UNESP] (Elsevier, 2024)
Tuberculosis is one of the major causes of death worldwide; more than a million people die every year because of this infection. The constant emergency of Mycobacterium tuberculosis resistant strains against the most used treatments also contributes to the burden caused by this disease. Consequently, the development of new alternative therapies against this disease is constantly required. In recent years, only a few molecules have reached the market as new antituberculosis agents. The mycobacterial cell wall biosynthesis is for a longstanding considered an important target for drug development. Particularly, in M. tuberculosis, the peptidoglycan cross-links are predominantly formed by nonclassical bridges between the third residues of adjacent tetrapeptides. The responsible enzymes for these reactions are LD-transpeptidases (Ldts), for which M. tuberculosis has five paralogues. Although these enzymes are distinct from the penicillin-binding proteins (PBPs), they can also be inactivated by β-lactam antibiotics, but since M. tuberculosis has a chromosomal β-lactamase, most of the antibiotics of these classes can be degraded. Thus, to identify alternative scaffolds for the development of new antimicrobials against tuberculosis, we have integrated several fragment-based drug discovery techniques. Based on that, we identified and validated a number of small molecules that could be the starting point in the synthesis of more potent inhibitors against at least two Ldts from M. tuberculosis, LdtMt2 and LdtMt3. Eight identified molecules inhibited the Ldts activity in at least 20%, and three of them have antimycobacterial activity. The cell ultrastructural analysis suggested that one of the best compounds induced severe effects on the septum and cell wall morphologies, which corroborates our target-based approach to identifying new Ldts hits.
Keywords: Fragment-based drug discovery; L,D-Transpeptidases; Mycobacterium tuberculosis; Tuberculosis